Highly active and thermally stable single-atom catalysts for high-temperature electrochemical devices - Shin, Jisu; Lee, Young Joo; Jan, Asif; Choi, Sung Min; Park, Mi Young; Choi, Sungjun; Hwang, Jun Yeon; Hong, Seung ki; Park, Seung Gyu; Chang, Hye Jung; Cho, Min Kyung; Singh, Jitendra Pal; et al. (Royal Society of Chemistry, 2020)
Single-atom catalysts provide unique catalytic properties and maximize the atom utilization efficiency. While utilizing them at elevated temperatures is highly desirable, their operating temperature is usually kept below 300 degrees C to prevent isolated atoms from agglomerating. Moreover, their applications in high-temperature electrochemical devices have been hindered by the lack of suitable processing techniques for catalyst loading. Herein, we report single-atom Pt/ceria nanocatalysts that are highly active and thermally stable in solid oxide cells (SOCs) operating at 600-800 degrees C. Our urea-based chemical solution process creates strong Pt-O-Ce interactions that securely anchor isolated Pt atoms to the surface of ceria nanoparticles and suppress their high-temperature migration. These single-atom Pt/ceria nanocatalysts are loaded in the oxide fuel electrode of a SOC via an in situ synthetic process, which reduces the polarization resistance from 28.2 to 0.82 Ohm cm(2) at 600 degrees C. This electrode outperforms the state-of-the-art Ni-based fuel electrode by up to 10 times and delivers extremely high performance in full SOCs in fuel cell and electrolysis modes. Furthermore, it stably operates at 700 degrees C for over 500 h under realistic operating conditions. Our results provide guidance to resolve the critical issues for the practical use of single-atom catalysts in various industrial processes and accelerate the commercial development of next-generation high-temperature energy devices.